THE ROLE OF PHYSICAL EDUCATION IN ORGANIZING A HEALTHY LIFESTYLE (IN DIFFERENT YOUTH GROUPS) - Oybek Abdurakhmonovich Parpiyev (Scholar Express Journal, 2022)
In the article the cultural and physical development along with cultural and physical development are studied in the article, the provision of precautionary measures and the prevention of injury during physical exercises are studied, physical education training from physical education work forms in different age groups and one of the results of independent physical exercises carried out in everyday life was developed, scientific proposal and practical recommendations were developed in relation to the development of factors to reduce children's fatigue and increase their work ability
Keywords: Healthy lifestyle; physical development; small and medium groups; building complexes